Organizational openness and attitudes toward hiring persons with disabilities in NCWDP member organizations - Dela Llana, Michelle May G. (Animo Repository, 2005)
This descriptive-correlational research study sought to describe the organizational openness and attitudes toward hiring PWDs and their correlation with selected variables. The study involved 41 employers and supervisors of establishments, included in the Directory of Employers Employing Persons with Disabilities of the National Council for the Welfare of Disabled Persons (NCWDP) in Metro Manila. The instrument utilized in the study was adapted from instruments made by Soriano (2004) on his research on Employers Attitudes Toward Deaf Workers and The Scale of Attitudes Toward Disabled Persons by Richard Antonak. The findings of the study provide a better understanding of the respondents basic personal and organization profiles, and how these variables can affect organizational openness and attitudes toward hiring PWDs. Results indicated that supervisors handling the PWDs are ambivalent in their attitude towards PWDs in general while organizational openness as expressed by the employers was positive. Organizational openness correlated significantly with the years of existence of the establishment and the type of disability hired specifically hearing impairment, mental retardation and speech impairment. There are no significant relationships however between the supervisors attitude and their personal characteristics and relationship with the PWD.